Afatinib for the treatment of non-small cell lung cancer. (2nd November 2015) - Biello, Federica; Maggioni, Claudia; Rijavec, Erika; Genova, Carlo; Barletta, Giulia; Gualco, Elisa; Truini, Anna; Coco, Simona; Dal Bello, Maria Giovanna; Vanni, Irene; Alama, Angela; Boccardo, Francesco; et al.
Abstract : Introduction: Tyrosine kinase inhibitors (TKI) are currently the most effective therapy for patients with NSCLC and common activating mutations of EGFR.Afatinib, an irreversible EGFR, HER2, and HER4 inhibitor, has recently been approved at the dose of 40 mg daily as front-line treatment for advanced NSCLC with common EGFR-activating mutations. Areas covered: The review analyzes the pharmacodynamics, pharmacokinetics, safety, and clinical efficacy of afatinb in NSCLC. This irreversible TKI was initially investigated in EGFR-unselected patients who progressed after TKIs, but the subsequent observation of its major activity against exon 19 mutant determined its indication in common EGFR mutations. Several Phase I to Phase III studies explored the role of afatinib in different settings of patients. Expert opinion: Afatinib showed efficacy as a front-line treatment in patients with EGFR common mutations. Currently, no statistically significant differences between afatinib, gefitinib, and erlotinib have been detected, as they all improve progression-free survival, disease control rate, and control of symptoms in NSCLC EGFR mutant patients; the pooled analysis of LUX-Lung 3 and 6 data in patients harboring Del19 is the only demonstration of a statistical improvement in overall survival with afatinib.